Copolymers of 2-(3-mesityl-3-methyleyclobutyl)-2-ketoethyl methacrylate with acrylonitrile and styrene: Synthesis, characterization, and monomer reactivity ratios - Erol, I; Ahmedzade, M (Springer, 2005)
The copolymerization of 2-(3-mesityl-3-methylcyclobutyl)-2-ketoethyl methacrylate monomer with acrylonitrile and styrene were carried out in 1,4-dioxane solution at 60 degrees C using AIBN as an initiator. The copolymers were characterized by Fourier transform infrared, H-1-NMR, and C-13-NMR spectroscopic techniques. Thermal properties of the polymers were also studied by thermogravimetric analysis and differential scanning calorimetry. The copolymer compositions were determined by elemental analysis and H-1-NMR technique. The monomer reactivity ratios were calculated by the application of conventional linearization methods as a result of Fineman-Ross and Kelen-Tudos to less than 1 for both monomers.
Keywords: copolymers; cyclobutane; ketoethyl methacrylate; monomer reactivity ratios